Meningkatkan Pemahaman Konsep Perubahan Wujud Benda pada Pembelajaran Ilmu Pengetahuan Alam Melalui Metode Eksperimen di Sekolah Dasar - Hikmah Mutmainnah (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2020)
The purpose of this research is to describe the improvement of concept understandingof scince subject through Experiment method of students low class. The type of research was Classroom Action Research (CAR) which was the design using Kemmis’s model and Mc Taggart  for two cycle. The population if this research was the third class for 24 students. Data collection of this research was using test, observation, and field’s note. The result of pre-cycle got 21% for concept understanding as clasical, it has the improrement of cycle I which was got 55% and for cycle II got 92%. The conclusion of this research is that the application of eksperiment method can improve studentd’s concept understanding of studying scince of low class in academic year 2018/2019.